The international collaborative on fatigue following infection (COFFI). Issue 2 (3rd April 2018) - Katz, Ben Z; Collin, Simon M; Murphy, Gabrielle; Moss-Morris, Rona; Wyller, Vegard Bruun; Wensaas, Knut-Arne; Hautvast, Jeannine L.A.; Bleeker-Rovers, Chantal P; Vollmer-Conna, Ute; Buchwald, Dedra; Taylor, Renée; Little, Paul; et al.
ABSTRACT: Background: The purpose of the Collaborative on Fatigue Following Infection (COFFI) is for investigators of post-infection fatigue (PIF) and other syndromes to collaborate on these enigmatic and poorly understood conditions by studying relatively homogeneous populations with known infectious triggers. Utilising COFFI, pooled data and stored biosamples will support both epidemiological and laboratory research to better understand the etiology and risk factors for development and progression of PIF. Methods: COFFI consists of prospective cohorts from the UK, Netherlands, Norway, USA, New Zealand and Australia, with some cohorts closed and some open to recruitment. The 9 cohorts closed to recruitment total over 3000 participants, including nearly 1000 with infectious mononucleosis (IM), > 500 with Q fever, > 800 with giardiasis, > 600 with campylobacter gastroenteritis (CG), 190 with Legionnaires disease and 60 with Ross River virus. Follow-ups have been at least 6 months and up to 10 years. All studies use the Fukuda criteria for defining chronic fatigue syndrome (CFS). Results: Preliminary analyses indicated that risk factors for non-recovery from PIF included lower physical fitness, female gender, severity of the acute sickness response, and autonomic dysfunction. Conclusions: COFFI (https://internationalcoffi.wordpress.com/ ) is an international collaboration which should be able to answer questions based on pooled data that are not answerable in the individual cohorts. Possible questions may include the following: Do different infections trigger different PIF syndromes (e.g. CFS vs. irritable bowel syndrome)?; What are longitudinal predictors of PIF and its severity?